Effects of iodinated contrast media in a novel model for cerebral vasospasm - Nikitina, Tatiana; Zavaritskaya, Olga (Arquivos de neuro-psiquiatria, 2015)
Objective: We developed an in vitro model for vasospasm post subarachnoid hemorrhage that was suitable for investigating brain vessel autoregulation. We further investigated the effects of iodinated contrast medium on the vascular tone and the myogenic response of spastic cerebral vessels. Method: We isolated and perfused the superior cerebellar arteries of rats. The vessels were pressurized and studied under isobaric conditions. Coagulated blood was used to simulate subarachnoid hemorrhage. The contrast medium iodixanol was applied intraluminally. Results: Vessels exposed to blood developed significantly stronger myogenic tone (65.7 ± 2.0% vs 77.1 ± 1.2% of the maximum diameter, for the blood and the control group, respectively) and significantly decreased myogenic response, compared with the control groups. The contrast medium did not worsen the myogenic tone or the myogenic response in any group. Conclusion: Our results show that deranged myogenic response may contribute to cerebral blood flow disturbances subsequent to subarachnoid hemorrhage. The contrast medium did not have any negative influence on vessel tone or myogenic response in this experimental setting.
DOI funktioniert nicht
Gesehen am 21.11.2018